Roles of Eicosanoids in Regulating Inflammation and Neutrophil Migration as an Innate Host Response to Bacterial Infections - Sheppe, Austin E F; Edelmann, Mariola J (Infection and immunity, 2021)
Eicosanoids are lipid-based signaling molecules that play a unique role in innate immune responses. The multiple types of eicosanoids, such as prostaglandins (PGs) and leukotrienes (LTs), allow the innate immune cells to respond rapidly to bacterial invaders. Bacterial pathogens alter cyclooxygenase (COX)-derived prostaglandins (PGs) in macrophages, such as PGE2 15d-PGJ , and lipoxygenase (LOX)-derived leukotriene LTB which has chemotactic functions. The PG synthesis and secretion are regulated by substrate availability of arachidonic acid and by the COX-2 enzyme, and the expression of this protein is regulated at multiple levels, both transcriptionally and posttranscriptionally. Bacterial pathogens use virulence strategies such as type three secretion systems (T3SSs) to deliver virulence factors altering the expression of eicosanoid-specific biosynthetic enzymes, thereby modulating the host response to bacterial lipopolysaccharides (LPS). Recent advances have identified a novel role of eicosanoids in inflammasome activation during intracellular infection with bacterial pathogens. Specifically, PGE was found to enhance inflammasome activation, driving the formation of pore-induced intracellular traps (PITs), thus trapping bacteria from escaping the dying cell. Finally, eicosanoids and IL-1β released from macrophages are implicated in the efferocytosis of neighboring neutrophils. Neutrophils play an essential role in phagocytosing and degrading PITs and associated bacteria to restore homeostasis. This review focuses on the novel functions of host-derived eicosanoids in the host-pathogen interactions.